2022
DOI: 10.1186/s12909-022-03892-9
|View full text |Cite
|
Sign up to set email alerts
|

Key tips to providing a psychologically safe learning environment in the clinical setting

Abstract: Having psychological safety embedded in preceptorship relationships facilitates positive interpersonal and educational experiences for students. Psychological safety refers to a student’s belief as to whether or not it is safe for them to take interpersonal risks, such as asking questions, sharing an idea for improvement or speaking up to maintain patient safety. Having psychological safety leads to collaboration, positive student learning experiences and effective patient care. This article presents key guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In addition, in order to measure, and enhance, psychological safety in mental health services, team-level surveys are administered that comprises proposed indicators of psychological safety as perceived compassion, as well as perceived institutional and managerial help [ 81 ]. Finally, it has been shown that among the key-points for ensuring a psychologically safe learning environment in a clinical context kindness represents a fundamental component [ 82 ]. Taken together, it may be hypothesized that these findings indicate that in order to develop, and maintain, psychological safety both self-compassion and self-kindness may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in order to measure, and enhance, psychological safety in mental health services, team-level surveys are administered that comprises proposed indicators of psychological safety as perceived compassion, as well as perceived institutional and managerial help [ 81 ]. Finally, it has been shown that among the key-points for ensuring a psychologically safe learning environment in a clinical context kindness represents a fundamental component [ 82 ]. Taken together, it may be hypothesized that these findings indicate that in order to develop, and maintain, psychological safety both self-compassion and self-kindness may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…53 However, in the context of a busy clinical setting with many potential distractors, creating this learning environment is difficult and requires a skillful preceptor who can balance autonomy and supervision, encourage open communication and provide constructive feedback. 54 Additionally, both the community preceptor and student need to be aware of the expectations from the clinical experience.…”
Section: Discussionmentioning
confidence: 99%
“…This begs the question, are preceptors creating a psychologically safe space for our learners? 27 The learner should be comfortable asking questions, making reasonable mistakes, and providing feedback as well as receiving feedback. Preceptors may be unaware of their own nonverbal cues that occur during student discussions such as eye rolling, looking away frequently, or distracting behavior.…”
Section: Preceptor Perceptions Of Power Dynamic Over Studentsmentioning
confidence: 99%
“…Some preceptors may compare one student to another in abilities, which may be a biased comparison that is not conducive to a positive learning environment. 27 All of these may give the impression to the learner that they are performing poorly or are not deserving of their preceptor's time and attention. Thus, they may not feel comfortable sharing this feedback and the preceptor's growth will be limited and the precepting patterns will continue.…”
Section: Preceptor Perceptions Of Power Dynamic Over Studentsmentioning
confidence: 99%
See 1 more Smart Citation